Estimating the programmatic cost of targeted mass drug administration for malaria in Myanmar - Kyaw, SS; Delmas, G; Drake, TL; Celhay, O; Pan-Ngum, W; Pukrittayakamee, S; Lubell, Y; Aguas, RJ; Maude, RJ; White, LJ; Nosten, F (BioMed Central, 2021)
Background Mass drug administration (MDA) has received growing interest to accelerate the elimination of multi-drug resistant malaria in the Greater Mekong Subregion. Targeted MDA, sometimes referred to as focal MDA, is the practice of delivering MDA to high incidence subpopulations only, rather than the entire population. The potential effectiveness of delivering targeted MDA was demonstrated in a recent intervention in Kayin State, Myanmar. Policymakers and funders need to know what resources are required if MDA, targeted or otherwise, is to be included in elimination packages beyond existing malaria interventions. This study aims to estimate the programmatic cost and the unit cost of targeted MDA in Kayin State, Myanmar.